Social Media Platforms and their Relevance in Providing Psychological Support among Infertility Patients - Lobo, Deepika; Joshi, Meenakshi; Sharma, Jyotika (Journal of Neonatal Surgery, 2025)
Infertility is a life-altering condition that often leads to psychological distress, including feelings of isolation, grief, and anxiety. Infertility is defined as the ‘failure to establish a clinical pregnancy after 12 months of regular and unprotected sexual intercourse’, affecting about 12–18% of women aged 18–44 years.(Lotti and Maggi, 2015; Vander Borght and Wyns, 2018).With the rise of social media, online platforms have become essential in providing emotional and psychological support to individuals coping with infertility. This paper explores the role of social media platforms in offering psychological support to infertility patients, focusing on the apps that are most commonly used and valued by individuals going through infertility treatments. The paper examines the features of these platforms, how they contribute to reducing emotional distress, and their potential benefits and limitations.